Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/acel.13130
|View full text |Cite
|
Sign up to set email alerts
|

IL10 deficiency promotes alveolar enlargement and lymphoid dysmorphogenesis in the aged murine lung

Abstract: The connection between aging‐related immune dysfunction and the lung manifestations of aging is poorly understood. A detailed characterization of the aging IL10‐deficient murine lung, a model of accelerated aging and frailty, reconciles features of both immunosenescence and lung aging in a coherent model. Airspace enlargement developed in the middle‐aged (12 months old) and aged (20–22 months old) IL10‐deficient lung punctuated by an expansion of macrophages and alveolar cell apoptosis. Compared to wild‐type (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated that AM isolated from healthy nonsmoking human volunteers activate the expression of IL-10 upon stimulation with LPS [ 62 ]. Additionally, loss of IL-10 has been attributed to significant morphological functional changes in aged mice [ 63 ]. This indicates that IL-10 is key mediator of IL-10 homeostasis in the murine lung with either low level constitutive or intermittent expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that AM isolated from healthy nonsmoking human volunteers activate the expression of IL-10 upon stimulation with LPS [ 62 ]. Additionally, loss of IL-10 has been attributed to significant morphological functional changes in aged mice [ 63 ]. This indicates that IL-10 is key mediator of IL-10 homeostasis in the murine lung with either low level constitutive or intermittent expression.…”
Section: Discussionmentioning
confidence: 99%
“…as shown in fig. 1, a noteworthy phenomenon was found, after cucurbitacin i administration, some of the shrunk cells that had attached to the culture dish still had cell viability and did not apoptosis is a form of programmed cell death that brings about the orderly and efficient removal of damaged cells, such as those resulting from dna damage or during development (25,26). The mechanism of apoptosis is very complex and numerous signaling pathways are involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Death was verified by observed cessation of breathing and heartbeat. Tissues were harvested, weighed, flash-frozen in liquid nitrogen and stored at −80°C as described ( Sikka et al, 2013 ; Malinina et al, 2020 ). All protocols were approved by the Johns Hopkins University Institutional Animal Care and Use Committee, and all experiments performed accordingly.…”
Section: Methodsmentioning
confidence: 99%
“…Because clinical frailty also strongly correlates with chronic inflammation, it is studied in a C57Bl/6 mouse model genetically deficient for the anti-inflammatory cytokine, Interleukin-10 (IL-10 B6.129P2- IL 10 tm/tm /J mice; Walston et al, 2008 ). These IL10 tm/tm (henceforth ‘IL10-KO’) mice experience lifelong chronic inflammation and exhibit multiple phenotypes consistent with human frailty including increased expression of NF-kB-dependent inflammatory mediators (e.g., IL-1β, TNFα, IFγ, IL-6, chemokine ligand-1; Walston et al, 2008 ; Ma et al, 2021 ) as well as age-associated reductions in strength, altered skeletal muscle gene expression, altered insulin signaling (high IGF-1), impaired mitochondrial degradation, high blood pressure, vascular stiffness, reduced fat, endothelial dysfunction, dysregulated tyrosine degradation and higher mortality ( Sikka et al, 2013 ; Westbrook et al, 2017 ; Lewsey et al, 2020 ; Malinina et al, 2020 ; Westbrook et al, 2020 ). Though primarily a model for chronic inflammation, IL10-KO mice are valuable for many purposes including the study of frailty.…”
Section: Introductionmentioning
confidence: 99%